Menggeser Paradigma Masyarakat Tentang Agama Di Tengah Pandemik Covid-19 Dalam Perspektif Hermeneutika Paul Ricoeur - Rosyid, Abdul (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Covid-19 is a new type of virus that has shocked the world community in recent months. Many effects of the virus must be borne, economic, political, religious are real forms that have become new phenomena. Covid-19 changes both social and religious orders, understanding of religious propositions must be renewed again considering the context of the phenomenon is different. Religious conflict in the midst of Covid-19 is the result of incomplete religious understanding, partial understanding, the effect of which is a puritanical religious practice. Paul Ricoeur's hermeneutics is a bridge to straighten the understanding of religious propositions that don't fit the context. Islam as a major religion in the world must be able to answer the problems of its people.